ANALISIS EFISIENSI PERBANKAN SYA RIAH DENGAN MENGGUNAKAN STOCHASTIC FRONTIER APPROACH PERIODE 2010–2014 - Indah Sukmaningrum; Hotman Tohir Pohan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2016)
This study aimed to analyze the technical efficiency and the relationshipbetween savings, total fixed assets, and labor costs for financing the Islamic Banks in Indonesia relating to the technical efficiency. This study uses secondary data by downloading BUS quarterly reports on directory OJK in 2015. The sample used in this study were 190 samples from 10 Islamic Banks since the second quarter of 2010 up to the end 2014. Panel data analysis using the method of Stochastic Frontier Approach orientation Cobb Douglas production function and see the bank with the intermediation approach. Causality data is processed using multiple regression equation with Cobb Douglas linear function. Based on the results of this study concluded that an efficient BUS with the highest technical and Bank Panin Syariah, BUS with the lowest technical efficiency is Bank Victoria Syariah. Based on the results of all the input variables affect the output variables. And the rise and fall of proven technical efficiency due to the influence of the variable relationship